Unlocking the Wealth From Benefit Sharing in Drill and Blast - Mike Wiggin; Lawrie Logan (International Society of Explosives Engineers, 2001)
This paper will be in two parts, a discussion of the benefits available from benefit sharing as a concept followed by an examination of how this approach was applied at Mesa J Mine and what improvements were made. The first part is an outline of the ways that both parties in a benefit sharing agreement can uncover additional wealth by bringing a new approach to the relationships between mine and supplier. The paper describes a partnering agreement recently established between Robe River Iron Associates (RRIA) and Dyno Nobel Asia Pacific Ltd (DNAP) to access the wealth locked up by the usual explosives supply contracts in Australia and elsewhere. The partners are acting cooperatively to maximise the benefits to both parties from optimising blasting practices at the Mesa J Iron Ore Mine in the Pilbara region of Western Australia.